3D shape evolution of microparticles and 3D enabled applications using non-uniform UV flow lithography (NUFL). Issue 40 (29th September 2017) - Choi, Kenneth; Salehizadeh, Mohammad; Da Silva, Rafael Belo; Hakimi, Navid; Diller, Eric; Hwang, Dae Kun
Abstract : The generation of microparticles with non-spherical morphologies has generated extensive interest because of their enhanced physical properties that can increase their performance in a wide variety of clinical and industrial applications. Abstract : The generation of microparticles with non-spherical morphologies has generated extensive interest because of their enhanced physical properties that can increase their performance in a wide variety of clinical and industrial applications. A flow lithographic technique based on stop flow lithography (SFL) recently showed the ability to fabricate particles with 3D shapes via manipulation of the UV intensity profile in a simple 2D microfluidic channel. Here, we further explore this flow lithographic method, called non-uniform flow lithography (NUFL), to investigate the 3D-shape tuning ability for the generation of 3D magnetic microparticles and their potential applications. We characterize the morphological microparticle shape change through variation of polymerization objective, UV intensity, and solution opacity. We also couple the particles' intrinsic anisotropic magnetic properties with an external magnetic field to create chains of bullet- and bell-shaped particles and a valve-like micromachine. In addition, in contrast to other complex and multi-step methodologies, NUFL shows a simple route for the facile creation of 3D microstructure platforms such as microneedles with fully modifiable tip morphology. This method presents intriguing possibilities for growing research within 3D microstructure assembly, micromachine systems and minimally invasive medical interventions.